Dynamical properties of a two-dimensional one-component plasma (2018)
The Two-Dimensional One-Component Plasma with log interactions is a fundamental model in many-body physics, whose equilibrium statistical mecha.nics has been widely studied. However, much has not been explored about its dynamic behavior. Therefore, the purpose of this work is to study the implementation of the Engineered Swift equilibration protocol (ESE) to different simple systerns of one body, to then approach the implementation in the plasma, starting from the simplest case N 1. Roughly,this method consist in speed up the transition between two equilibrium states finding out the proper (wolution of a determined control parameter